Spinal neuraxial anaesthesia for Caesarean section in a parturient with Type I Arnold–Chiari malformation and syringomyelia. (June 2019) - Teo, Mavis Miqi
Type 1 Arnold–Chiari Malformation is associated with prolapse of the cerebellar tonsils into or below the level of the foramen magnum and is usually diagnosed in adults. There are no current guidelines for the management of patients with a residual Type I Arnold–Chiari Malformation, planned for a Caesarean section under spinal neuraxial anaesthesia. The paucity of literature on this topic presents as a management dilemma. We report a case of a term parturient with Type 1 Arnold–Chiari Malformation, following surgical decompression four years earlier, with a residual syringomyelia who underwent an elective Caesarean section under spinal neuraxial anaesthesia. This case highlights that multidisciplinary management and an early anaesthetic consult is of paramount importance in the outcome of the patient, and that spinal neuraxial anaesthesia can be considered as a safe anaesthetic option.